Shadow kiss - Mead, Richelle (London : Penguin Books, 2013)
Shadow-kissed Rose is hunted by the immortal undead that are seeking vengeance on her for her Strigoi kills, which puts her in a terrible position that could result in the death one of the two people she values most, her best friend Lissa, or her tutor Dimitri Belikov, the man she loves.
9
Young Adult.
Young Adult
Keywords: High schools -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; Social classes -- Juvenile fiction; Vampires -- Juvenile fiction; High schools -- Fiction; Magic -- Fiction; Schools -- Fiction; Social classes -- Fiction; Vampires -- Fiction; High schools -- Fiction; Magic -- Fiction; Occult fiction; School stories; Social classes -- Fiction; Vampires -- Fiction; Occult fiction